曲轴表面激光冲击强化的数值仿真 - 王红军 (Jixie chuandong)
Effect of laser impacting reinforcement on the residual stress distribution of fillet for the diesel engine crankshaft is analyzed by ANSYS finite element analysis software.The simulation results are compared with the experimental data,the simulation results are basically consistent with the experimental data.The finite element simulation method and related simulation parameters are correct is proved.The parameters of laser impacting reinforcement are optimized by ANSYS simulation,and the residual stress favorable distribution of the crankshaft fillet is obtained.